Influence of operational conditions and wastewater properties on the removal of organic micropollutants through ozonation. (15th May 2021) - Ekblad, M.; Juárez, R.; Falås, P.; Bester, K.; Hagman, M.; Cimbritz, M.
Abstract: The objective of this study was to evaluate the influence of operational conditions and wastewater properties on the removal of pharmaceuticals, contrast media and antibiotics through ozonation, in order to facilitate the optimization of treatment and its implementation on a full scale. Pilot-scale ozone oxidation trials were performed on treated wastewater, before and after post-precipitation, over a seven-month period, including summer and winter months. Hydraulic retention times as short as 7 min were found to be sufficient for organic micropollutant removal. A short hydraulic retention time reduces both investment costs and land use. Neither the choice of ozone dispersion method, a static mixer or a Venturi injector, nor the wastewater temperature had any significant effect on the removal efficiency of organic micropollutants, however, higher removal was achieved after on-site post-precipitation with aluminum chloride. Highlights: Seasonal temperature variation (13–21 °C) had no effect on ozonation on pilot scale. An HRT as short as 7 min was sufficient for organic micropollutant removal. Ozone dispersion using a static mixer or a Venturi injector gave similar efficiency. Higher removal was achieved after post-precipitation with AlCl3 than before.